British Medical Journal. Supplement : A general medical service for the nation ([London : British Medical Association])
1938-04-30 1938 1930s 14 pages APRIL 30, 1938 GENERAL MEDICAL SERVICE FOR THE NATION SUPPLEMENT TO THE BRITISH MEDICAL JOURNAL 259 those whose reputation as a profession is involved in the manner in which they exercise collective responsibility entrusted to them. (b) Other Non-institutional Services 52. The Content of the Service. — Under the existing scheme all insured persons enjoy, as a statutory medical benefit, a general practitioner service and a cash benefit in respect of maternity; many, but not all, insured persons enjoy, as additional treatment benefits, financial payments in respect of dental and ophthalmic treatment, convalescent home treatment, medical and surgical appliances, and, to a much smaller extent, hospital accommodation and certain other benefits. The additional treatment benefits vary with each approved society (there are over 6,000 societies), and, where they are available, they are paid within the limits of the sum of money allocated for the purpose for the year in question. In the case of dental benefit approximately two-thirds of the present insured population belong to societies giving, under certain conditions, dental benefit, and in most cases members find half the cost themselves. Rather less than two-thirds of the insured population belong to societies giving ophthalmic benefit; in many cases this amounts only to a proportion of the cost of treatment or of spectacles. 53. In the view of the medical profession full dental and ophthalmic services should, in the interests of national health, be available in the extended service as statutory medical benefits to which all are entitled and which are administered together with other statutory medical benefits. In a national health service there should be made available the services of consultants and specialists in all branches of medicine, and facilities for radiological and pathological examinations. 54. Specialist services in tuberculosis, venereal disease, infectious disease and, in a number of areas, in obstetrics and in pathology (the last service varying from one limited to the examination of swabs and sputa to a fairly full service), are already provided by local authorities. The services in tuberculosis, venereal disease, and infectious disease have proved highly satisfactory, and for a number of reasons it is desirable that they should continue in their existing form as special services co-ordinated with, but not necessarily merged into, the main consultative arrangements. The obstetric service is dealt with in the sections relating to a national maternity service; its relationship to the general consulting service would depend on that between the maternity service and the extended insurance service. 55. It is proposed that the consultant and specialist service should be comprehensive and include all necessary facilities in medicine, surgery, obstetrics, and their special branches, as well as pathological and radiological services. It is suggested that the consultant and specialist service to be available should be defined as such examination as can be given at a single consultation, together with a report, where necessary, for the information of the attending practitioner. The service should be identical with that now available to private patients, and would be rendered, as a rule, in the consulting-room of the consultant or in the home of the patient. Although the approach of the patient to the general practitioner should be direct and free, it is essential, in the interest of the patient, that consultant and specialist services should be available only on the recommendation of the family doctor. 56. Personnel. — It would be necessary to establish lists of consultants and specialists who satisfy a certain standard of eligibility and who desire to render service under the scheme. There exists in the regulations of the existing insurance service a set of criteria which are admirably suited for the purpose. Before becoming eligible for inclusion on the lists the practitioner should satisfy a representative committee of medical practitioners that: (a) He has held hospital or other appointments affording special opportunities for acquiring special skill and experience of the kind required for the performance of the service rendered, and has had actual recent practice in performing the service rendered or services of a similar character; or (b) He has had special academic or postgraduate study of a subject which comprises the service rendered, and has had actual recent practice as aforesaid ; or (c) That he is generally recognized by other practitioners in the area as having special proficiency and experience in a subject which comprises the service rendered. 57. All practitioners satisfying one or more of the criteria (a), (b), and (c) should be eligible to have their names included in the lists. In the published lists the names should be divided into two classes: (1) those practising exclusively as consultants or specialists ; (2) those not practising exclusively as consultants or specialists. 58. Administration. — The consultant service should be administered by the statutory bodies responsible for the service as a whole. It is suggested that representative local medical bodies should be appointed to examine and report on the qualifications and experience of applicants for inclusion in the list, by reference to the criteria, and that a central professional body should be established for the consideration of appeals. 59. When a general practitioner decides that a consultation is desirable he himself should make the necessary arrangements direct with the consultant. If he is unable to be present at the consultation he should furnish a written report to the consultant, who, after the consultation, should report to the general practitioner. If the consultation takes place at the patient's house the attending general practitioner would normally be present. (c) Institutional Services 60. As a result of the interplay of many factors — social, scientific, and legislative — the hospital situation in this country has become exceedingly complicated. The voluntary hospital, which at one time was primarily the place in which the poor could obtain the treatment they needed, is to-day serving a class which constitutes four-fifths of the community. Formerly it provided a complete medical service for the poor: now it offers a specialized service to the great majority of the population, comprising not only the poor but those who can and do pay, in part or in whole, for the service they receive. Although the income from charitable sources is still considerable, the payments to voluntary hospitals by or on behalf of patients treated, made directly or by contributory schemes or local authorities, have in recent years risen greatly, and in 1935 they constituted nearly 40 per cent. of the total income in London and nearly 60 per cent. in the provinces. No fewer than ten million persons are covered by existing contributory schemes. 61. Until 1930 the voluntary hospital was the main agency providing an institutional service of a specialist character. As a result of the Local Government Act, 1929, it has now been joined in this field by county and county borough councils. Under the Poor Law there had in 100 years grown up a system of institutional provision which had a bed capacity approximately twice that of the voluntary hospital. This provision, however, was available not to the community generally but only to those who could satisfy the criterion of destitution; in fact, it was used largely for the chronic sick. The Local Government Act of 1929 transferred these institutions to the administrative control of county councils and county borough councils, giving them at the same time power to remove these institutions from their Poor Law associations. In the large towns local authorities have not been slow to exercise these powers, while in the counties there are signs of greater activity in this direction. There has thus appeared a new and powerful agency in the sphere of hospital activity. 292/847/1/60